INTELLECTUAL DEVELOPMENT AND EDUCATIONAL SUCCESS (Web of Teachers: Inderscience Research, 2024)
This artitsle dissusses ways to explore and develop a child’s level of mental development, which is one of the fasters that influences school sutssess and mainly predetermines a student’s learning diffusates.